2023
DOI: 10.7717/peerj.15437
|View full text |Cite
|
Sign up to set email alerts
|

Identifying C1QB, ITGAM, and ITGB2 as potential diagnostic candidate genes for diabetic nephropathy using bioinformatics analysis

Abstract: Background Diabetic nephropathy (DN), the most intractable complication in diabetes patients, can lead to proteinuria and progressive reduction of glomerular filtration rate (GFR), which seriously affects the quality of life of patients and is associated with high mortality. However, the lack of accurate key candidate genes makes diagnosis of DN very difficult. This study aimed to identify new potential candidate genes for DN using bioinformatics, and elucidated the mechanism of DN at the cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The current study verified the increased expression of ITGAM in the kidney tissue of DN mice using immunohistochemistry, confirming the potential role of ITGAM in the development of DN. A recent study confirmed the high expression of ITGAM in blood and kidney tissue in a diabetic renal rat model using reverse transcription quantitative polymerase chain reaction, which was consistent with the results of the current study 38 .…”
Section: Discussionsupporting
confidence: 92%
“…The current study verified the increased expression of ITGAM in the kidney tissue of DN mice using immunohistochemistry, confirming the potential role of ITGAM in the development of DN. A recent study confirmed the high expression of ITGAM in blood and kidney tissue in a diabetic renal rat model using reverse transcription quantitative polymerase chain reaction, which was consistent with the results of the current study 38 .…”
Section: Discussionsupporting
confidence: 92%
“…Integrin subunit alpha M (ITGAM), also known as complement component 3 receptor alpha chain (CD11b), or macrophage receptor 1 alpha subunit (Mac-1), is a cell-surface receptor that preferentially exists in myeloid leukemia cells ( 10 ). This protein not only mediates activation and effector responses, but also regulates leukemia cell-microenvironment interactions through ligand binding ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%